EFEKTIFITAS METODE SIMULASI DAN FEEDBACK YANG KONSTRUKTIF DALAM PELATIHAN CARDIOPULMONARY RESPIRATORY UNTUK MENINGKATKAN PENGETAHUAN DAN KETERAMPILAN MAHASISWA - Sugiarto Sugiarto; Sri Sundari; lisa musharyanti (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2020)
Constructive feedback is an effort to increase knowledge and skills so that instructors can find out how to provide constructive feedback. Constructive feedback of simulation methods needs to be given to students in order that they are motivated to increase their knowledge and skill. The objective of this study is to understand increasing of student’s knowledge and skill in simulation methods with and without constructive feedbacks. Methods used in this study is Quasi Experiment using pretest and posttest with control group. Total respondents used in this study are 77 respondents with 40 students of intervention group and 37 students of control group using purposive sampling technique. Respondents were given interventions such as constructive feedback.The results of study using paired sample t-test indicate that there was significant effect on giving constructive feedback to students before and after giving interventions with p-value result of 0.05. It is expected that feedback is continuously given by an educator to grow learning spirit and self-introspection to students.